CRISPR-Cas13a Targeting the Enhancer RNA-SMAD7e Inhibits Bladder Cancer Development Both in vitro and in vivo - Che, Wenan; Ye, Shanting; Cai, Aoxiang; Cui, Xiaojuan; Sun, Yuandong (Frontiers in Molecular Biosciences, 2020)
Enhancers are cis-acting elements that can promote the expression of target genes and respond to estrogen to induce the transcription of eRNAs, which are closely associated with cancer development. Further study on eRNAs may lead to a better understanding of the significance of transcriptional regulation and the progression of malignant tumors. SMAD7 enhancer RNA (SMAD7e) is an estrogen-responsive eRNA. However, the relationship between SMAD7e and bladder cancer remains unclear.SMAD7e was significantly upregulated in bladder cancer tissues and estrogen-stimulated cells. Knockdown of SMAD7e by CRISPR-Cas13a suppressed cell proliferation and migration, and induced cell apoptosis and inhibited cell invasion. Estrogen caused overexpression of SMAD7e and played a facilitating role in bladder cancer cells. Furthermore, knockdown of SMAD7e by CRISPR-Cas13a prevented the cancer-promoting effects of estrogen on bladder cancer both in vitro and in vivo. The present study suggested the crucial role of SMAD7e in bladder cancer. Estrogen might promote the development of bladder cancer by inducing SMAD7e production. These findings may provide a potential target for CRISPR-mediated gene therapy for bladder cancer in the future.